The Efficacy and Safety of Busulfan-Etoposide-Melphalan Regimen in Autologous Stem Cell Transplantation in Relapsed/Refractory Hodgkin and Non-Hodgkin Lymphoma Patients: -A Single-Center Experience- - ESER, ALİ; ESER, ALİ; Timuragaoglu, Aysen (My University, 2021)
Introduction: High-dose chemotherapy fol lowed by autologous stem cell transplantation (ASCT) is the standard treatment for relapsed and refractory lymphoma patients. The difficulties in accessing and high cost of carmustine have led to the increased use of alternative regimen before ASCT for the treatment of lymphoma, including busulfan-based busulfan-etoposidemelphalan (BuEM) regimens.